MRI analysis of extra-capsular ganglia at the gastrocnemius origin and their association with osteoarthritis. Issue 9 (September 2018) - Park, C.; Ahn, J.M.; Kim, H.; Kang, Y.; Lee, E.; Lee, J.W.; Kang, H.S.
Abstract : Aim: To evaluate the prevalence, clinical relevance, and magnetic resonance imaging (MRI) features of extra-capsular ganglia at the gastrocnemius origin and to assess their association with internal derangement and osteoarthritis of the knee. Materials and methods: One hundred consecutive knee MRI examinations, obtained within a 6-month period from patients with no history of recent knee trauma, recent injections, inflammatory arthritis, infection, or tumours, were evaluated retrospectively for the presence of ganglia at the gastrocnemius origin. The lesions were divided into two groups: an intra-capsular and an extra-capsular group. Cyst morphology (size, shape, and internal septa), internal derangement of the knee (cartilage lesion, cruciate ligament injury, meniscal tear, and corner injury on MRI, and osteoarthritis of the knee on radiographs) were evaluated. The chi-square, Fisher's exact, and t -tests were used to compare the two groups, in addition to multivariate stepwise logistic regression analysis. Results: Thirty-nine ganglia with an extra-capsular location were identified on 100 knee MRI (39 %). Rounded shape and internal septa were more common in the extra-capsular than in the intra-capsular group ( p <0.001). Frequencies of high-grade cartilage, meniscal tear, and high-grade osteoarthritis significantly differed between the groups ( p ≤0.038). In multivariate analysis, the only significant association was between high-grade osteoarthritis and the extra-capsular group. Conclusion: Extra-capsular ganglia at the gastrocnemius origin were not uncommon on knee MRI and had features typical of ganglia found at other sites. High-grade osteoarthritis was significantly associated with extra-capsular ganglia. Highlights: Extracapsular ganglia at the gastrocnemius origin were common on knee MRI. High-grade osteoarthritis is associated with extracapsular ganglia. Intra and extracapsular ganglia may reflect stages in the progression of degeneration.